Effects of Four Days of Competition Modelling Followed by Six Days of Tapering on Sport Performance in Junior Golfers: a Case Study - Marius Zienius; Antanas Skarbalius; Aurelijus Kazys Zuoza (Lithuanian Sports University, 2018)
Background. The use of competition modelling or tapering to improve sport performance in golf has not been extensively studied. Due to the specific conditions of the main competition, the simulation of competition modelling followed by tapering has been suggested as a means of improving junior golfers' sport performance. The aim of this study was to determine the most suitable precompetition model and taper for junior golfers to optimize their performance. Methods. Two male golfers (subject A: age 17 years, height 1.75 m, body mass 62 kg, basal heart rate 60 beats⋅min -1 , handicap index 10.1; subject B: age 17 years, height 1.87 m, body mass 68 kg, basal heart rate 60 beats⋅min -1 , handicap index 11.2) participated in this study. Sport performance indicators in golf were recorded using a personal sport performance statistical protocol. Locomotion and physiological demands were recorded using the FRWD W 400  Series (Finland) device. Furthermore, tapering training programmes were recorded. Results. The simulation of four days of competition modelling followed by six days of tapering allowed the subjects to improve their performance; their scoring average at the Lithuanian Amateur Open Golf Championship 2011 was by 6.02% (subject A) and 3.77% (subject B) lower than that for the four-day competition modelling stage. Conclusions. Findings suggest the effectiveness of four days of competition modelling, which allowed the simulation of the specific conditions of the main competition, and also of the practice round held three days before  the competition for junior golfers. Keywords: golf, simulation, locomotion, physiological demands, training loads.